The Relationship of Globalization, Internationalization and State Building in the Modern World - Людмила Новоскольцева (Історико-політичні проблеми сучасного світу, 2021)
The progress of globalization over the last few years has caused academic and political discussion worldwide. The opinions of experts and politicians vary on the nature of globalization, its driving forces, and consequences for civilization, nevertheless, the overwhelming majority of scholars agree that globalization is a key concept that ensures understanding of the essence of the transition of human society into the third millennium and the most demanded means of comprehending the essence of transformations of the world order at the turn of the 21st century. Globalization itself is a global problem of paramount importance, holding unique opportunities and existential threats. It opens fascinating prospects, and at the same time aggravates old diseases, and creates new threats and dangers. One of the most pressing issues of contemporary political science is whether the institution of the state will remain in the global world order, or whether it is doomed to be abolished by globalization. The wide variety of opinions and methodological approaches to the study of the phenomenon of globalization testifies that this phenomenon can be understood only by means of a comprehensive study of its main aspects.